Institutional complexity and private authority in global climate governance: the cases of climate engineering, REDD+ and short-lived climate pollutants. Issue 4 (4th July 2017) - Zelli, Fariborz; Möller, Ina; Asselt, Harro van
ABSTRACT: How and why do institutional architectures, and the roles of private institutions therein, differ across separate areas of climate governance? Here, institutional complexity is explained in terms of the problem-structural characteristics of an issue area and the associated demand for, and supply of, private authority. These characteristics can help explain the degree of centrality of intergovernmental institutions, as well as the distribution of governance functions between these and private governance institutions. This framework is applied to three emerging areas of climate governance: reducing emissions from deforestation and forest degradation (REDD+), short-lived climate pollutants (SLCPs) and climate engineering. Conflicts over means and values, as well as over relatively and absolutely assessed goods, lead to considerable variations in the emergence and roles of private institutions across these three cases.